A synergistic of pectinase, cellulase, and glucoamylase on anthocyanin content and extraction yield of roselle petals (Hibiscus sabdariffa L.) - Mardiah Mardiah; Noli Novidahlia; Ma’rifat Khoirunnisa; Hanafi Hanafi; Aminullah Aminullah (Jurnal Teknologi & Industri Hasil Pertanian, 2021)
The Roselle petals contain anthocyanin pigment which functions as an antioxidant and a natural food colorant. The objective of this research was to study the effect of three enzymes: pectinase, cellulase, and glucoamylase, on the quality of the extract of the Roselle petals. The fresh and dried Roselle petals were extracted using distilled water in a ratio of 1:4 and divided into five parts, in which each part was added by pectinase (P) of 1000ppm; pectinase and cellulase (PC) of 500:500ppm; pectinase and glucoamylase (PG) of 500:500ppm; and pectinase, cellulase and glucoamylase (PCG) of 333:333:333ppm, and without enzyme (TE) as a control. Furthermore, 1% of citric acid was added to all treatments. Determination of the chosen treatment used was based on residue extract, anthocyanin analysis, and the pH value. The results showed that fresh Rosella extract with PC has a yield value of 7.60% and it was not significantly different from the extract with PCG which yielded 7.37%.  Dried Rosella extract with PCG had the highest yield of 22.10% compared to the control (without enzyme) of 12.96%. However, the PCG addition generated a sticky product. Both fresh and dried Roselle extracts with PC contained the highest anthocyanin content of 156.64±1.30mgL-1 and 35.09±0.04 mgL-1, respectively. The pH values of fresh and dried Roselle extracts were 2.65 and 2.24, respectively. This research showed that the treatment of fresh and dried Roselle petals with the addition of  P, PC, or PCG increased the extraction yield value. Additionally, these enzymes could also increase the anthocyanin content of the extracts.